Inventory of moraine-glacial lakes of the Shilik river basin and analysis of their spatial distribution (Journal of Geography and Environmental Management, 2022)
Nowadays Central Asia faces the challenge of addressing the challenges posed by climate change. Due to the increase in the temperature background, the active thermocarial processes lead to an annual increase in the number of moraine lakes and their areas. Insufficient information on the current state of the glacial and moraine lakes complex and their inventory and classification is one of the factors hindering the planning of the farm, the necessary construction work, disaster preparedness and risk assessment strategies and mitigation strategies. Detection and identification of moraine lakes in the Shilik River Basin was carried out on the basis of Google Earth module 9.x, remote sensing of the Earth and the use of GIS technology. The article identifies 143 lakes with a total area of ​​5.71 km2, located in the middle and high mountain zones of the Kungei and Ili Alatau ridges, based on the space imagery in recent years in the Shilik River basin. In addition, the data of remote sensing of the Earth allowed to determine the area of ​​the lake basins, their types and location features.